2018
DOI: 10.1002/elan.201800100
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of CNT‐doped Imine Based Receptors as Fe(III) Sensor Using Potentiometry and Voltammetry

Abstract: A highly sensitive and selective potentiometric and voltammteric assay for the detection of Fe3+ using (E)‐3‐((2‐(2‐(2‐aminoethylamino) ethylamino) ethylimino)methyl)‐4H‐chromen‐4‐one (IFE(III)) ionophore was developed. To demonstrate the ion‐to‐electron transfer ability of MWCNT, these were incorporated in the ion‐selective membrane and response characteristics of Fe3+ electrode was compared with those of the traditional ion selective electrode. The electrode showed an improved Nernstian slope, lower detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
5
0
3
Order By: Relevance
“…) ethylamino) ethylimino)methyl)-4H-chromen-4-one, as an ionophore for potentiometric Fe 3+ sensing. 142 The prepared Fe 3+ -selective electrode with an inner reference solution demonstrated a 21 mV/ decade slope in the concentration range of 10 −6 −10 −1 M. Surprisingly, the authors reported that the additional doping of the membrane matrix with carboxylated MWCNTs improved the lower detection limit of their sensor by almost an order of magnitude. Besides, the MWCNT doping also lowered the selectivity coefficient values for Fe 3+ over different cations by 1−2 orders of magnitude.…”
Section: Mittal Et Al Synthesized and Tested An Imine-based Ligand (E...mentioning
confidence: 98%
See 1 more Smart Citation
“…) ethylamino) ethylimino)methyl)-4H-chromen-4-one, as an ionophore for potentiometric Fe 3+ sensing. 142 The prepared Fe 3+ -selective electrode with an inner reference solution demonstrated a 21 mV/ decade slope in the concentration range of 10 −6 −10 −1 M. Surprisingly, the authors reported that the additional doping of the membrane matrix with carboxylated MWCNTs improved the lower detection limit of their sensor by almost an order of magnitude. Besides, the MWCNT doping also lowered the selectivity coefficient values for Fe 3+ over different cations by 1−2 orders of magnitude.…”
Section: Mittal Et Al Synthesized and Tested An Imine-based Ligand (E...mentioning
confidence: 98%
“…Mittal et al synthesized and tested an imine-based ligand, ( E )-3-((2-(2-(2-aminoethylamino) ethylamino) ethylimino)­methyl)-4 H -chromen-4-one, as an ionophore for potentiometric Fe 3+ sensing . The prepared Fe 3+ -selective electrode with an inner reference solution demonstrated a 21 mV/decade slope in the concentration range of 10 –6 –10 –1 M. Surprisingly, the authors reported that the additional doping of the membrane matrix with carboxylated MWCNTs improved the lower detection limit of their sensor by almost an order of magnitude.…”
Section: Sensor Materialsmentioning
confidence: 99%
“…It can be seen in Table 2 that interferences with metal ions including Na + , K + , Mn 2+ , Zn 2+ , Ni 2+ , Co 2+ Fe 2+ , and Cr 3+ are negligible for the developed electrodes since the selectivity coefficient values were lower than 1 (22).…”
Section: Interference Studymentioning
confidence: 99%
“…Therefore, how to quickly and accurately detect Fe 3+ in the environment has always attracted much attention [13]. At present, there are many detection methods for Fe 3+ , including potential voltammetry [14], atomic absorption spectrometry [15], and colorimetric methods [16]. However, most of these testing methods require expensive tools or instruments, and the more complex testing processes also put forward higher technical requirements for sample processing and operation.…”
Section: Introductionmentioning
confidence: 99%